Using Think Pair Share Strategy to Improve Students’ Writing Comprehension Achievement - Akhmad Nuris Hidayat; Nabila Rifdah (Mastery: Master of English Language Journal, 2024)
Writing is one of the language skills that must to be mastered by the students, but writing is considered as one of the difficult skills to master. Think Pair Share strategy is a cooperative discussion strategy developed by Frank Lyman that creates a more active process, helps to maintain attention and improve the students’ motivation. In this research, the problem of the research could be formulated: How can Think Pair Share strategy improve and motivate the tenth students’ writing comprehension achievement at MA Al Misri Curahmalang 2023/2024  academic year? The hypothesis of the research were formulated: Think Pair Share (TPS) strategy can improve and motivate the tenth  students’ writing comprehension achievement at MA Al Misri Curahmalang 2023/2024  academic year. The design of this research is classroom action research. This research method is done in collaborative with the English teacher with sequence steps, namely the planning of the action, implementation of the action, observation, and reflection The result of the score analysis, ( M= 60. 27) in the first cycle to (M=70.06) in the second cycle, and the percentage of students ( ≥ 65 is 61.11%) in the first cycle to ( ≥ 65 is 87.04%) in the second cycle.